Coastal wetland adaptability to sea level rise: The neglected role of semi‐diurnal vs. diurnal tides. Issue 2 (26th January 2023) - Belliard, Jean‐Philippe; Gourgue, Olivier; Govers, Gerard; Kirwan, Matthew L.; Temmerman, Stijn
Abstract: Tidal marshes and mangroves are threatened by relative sea level rise (RSLR) in certain regions on Earth. Elsewhere, these coastal wetlands can adapt through sediment accretion and resulting surface elevation gain. Studies identifying drivers of the global variability in coastal wetland adaptability to RSLR ignored the role of the tidal pattern, varying from semi‐diurnal to diurnal globally. Here, we present a meta‐analysis, including 394 marsh and mangrove sites worldwide, and demonstrate that the tidal pattern explains ~ 25% of the variability in wetland elevation response to RSLR. Using a numerical model, we illustrate that less frequent, diurnal tides trigger lower sediment accretion rates, hence higher wetland vulnerability to RSLR, for various values of RSLR rates, tidal range and sediment supply. Our findings reveal a previously overlooked but relevant driver of coastal wetland adaptability to RSLR and call for new research as tidal patterns may affect other wetland ecosystem functions and services.